2017
DOI: 10.18632/oncotarget.14428
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the malignant phenotype by β-subunit selective noncovalent inhibition of immuno- and constitutive proteasomes

Abstract: A structure-based virtual screening of over 400,000 small molecules against the constitutive proteasome activity followed by in vitro assays led to the discovery of a family of proteasome inhibitors with a sulfonyl piperazine scaffold. Some members of this family of small non-peptidic inhibitors were found to act selectively on the β2 trypsin-like catalytic site with a preference for the immunoproteasome β2i over the constitutive proteasome β2c, while some act on the β5 site and post-acid site β1 of both, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 58 publications
(87 reference statements)
0
9
0
1
Order By: Relevance
“…It was analyzed by Lineweawer–Burk plots that showed a mixed inhibition mechanism (Figure c.). Such an allosteric modulation of the proteasome activity, already observed with non‐peptide inhibitors[42b], and also peptide inhibitors, indicated that binding occurred at a site other than the ChT‐L active site, while resulting in inhibition of enzyme activity.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…It was analyzed by Lineweawer–Burk plots that showed a mixed inhibition mechanism (Figure c.). Such an allosteric modulation of the proteasome activity, already observed with non‐peptide inhibitors[42b], and also peptide inhibitors, indicated that binding occurred at a site other than the ChT‐L active site, while resulting in inhibition of enzyme activity.…”
Section: Resultsmentioning
confidence: 67%
“…Three peptide proteasome inhibitors bearing an electrophilic warhead are currently marketed for the treatment of multiple myeloma, a blood cancer . In order to circumvent peptide limitations in therapy, the development of non‐peptide inhibitors, especially heterocyclic compounds, is growing ,. [51a], [51b], [51c], [51d], The heterocyclic structure of the prepared tryptanthrins 1‐R and their described cytotoxicity prompted us to test their ability to inhibit purified human constitutive 20S proteasome in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell viability was evaluated using the MTT assay, as previously described [45]. Control and MDA-MB-231 ppFurin cells were plated in 96-well microtiter plates respectively at a density of (1 × 10 4 /ml) cells/well.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…3-4) [18][19][20][21][22][23][24], and pseudopeptides [25][26][27] (Figure 2). Nonpeptidic noncovalent inhibitors have also been described (e. g. sulfonamides [28][29][30][31], hydroxyurea [32], 1,2,4-oxadiazoles [33], pyrazoles [34], phakellins [35], quinolines [36], psoralene [37]). The three approved covalent drugs inhibit mainly the β5 activity of the M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 catalytic core of the constitutive proteasome (cCP) but also that of the inducible immunoproteasome (iCP).…”
Section: Introductionmentioning
confidence: 99%